Evidence of Increased Oxidative Stress in the Placental Tissue of Women Who Suffered an Episode of Psychosis during Pregnancy - Miguel A. Ortega; Oscar Fraile-Martinez; Cielo García-Montero; Sonia Rodriguez-Martín; Rosa M. Funes Moñux; Coral Bravo; Juan A. De Leon-Luis; Jose V. Saz; Miguel A. Saez; Luis G. Guijarro; Guillermo Lahera; Jorge Monserrat; et al. (Antioxidants, 2023)
Psychosis is a complex clinical syndrome resulting in a loss of contact with reality and alterations in behavior and sensorial and motor functions. Although the onset of psychosis can be related to any medical condition, most cases of psychosis are not fully understood. Psychosis may manifest for the first time during pregnancy, which is detrimental to maternofetal well-being. The impact of having a first episode of psychosis during pregnancy on the placenta has not yet been explored. Oxidative stress is thought to take part in the etiopathogenesis of this complex disorder, and this condition can also affect the placenta as it is highly sensitive to changes in the maternal environment. In this sense, the aim of the present work was to study the gene and protein expression through RT–qPCR and immunohistochemistry, respectively, of oxidative stress markers (NOX-1, NOX-2, iNOS, eNOS and PARP) in the placental tissue of women who underwent a first episode of psychosis during pregnancy (FE-PW) in comparison to healthy pregnant women. Our results showed augmented gene and protein expression of NOX-1, NOX-2, iNOS and PARP in the placental tissue of FE-PW. For the first time, we demonstrated that oxidative stress may have an important pathophysiological role in this tissue, aiding in explaining the impact of psychosis on pregnancy and the need for future studies in this field to guide better clinical management of these patients.